Pendidikan Sains Berorientasi Keterampilan Abad 21 dalam Konteks Pendidikan Tinggi: Review - Yunita, Lintang; Mandasari, Nining (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This research is a literature review aimed at analyzing the concept and application of 21st-century skills-oriented science education in the context of higher education. 21st-century science education emphasizes the development of critical skills such as problem-solving, collaboration, communication, creativity, and digital literacy, which are considered essential for facing global challenges and rapid technological advancements. This study identifies trends, approaches, and challenges faced in integrating these skills into the science education curriculum at higher education institutions. Based on an analysis of various literature, it was found that although there are efforts to design learning that develops these skills, their implementation still faces various obstacles, such as limited resources, resistance to curriculum changes, and a lack of training for educators. This research provides recommendations for the development of policies and learning strategies that better support the integration of 21st-century skills in science education at the higher education level. The use of digital technology can enrich students' learning experiences and provide broader access to educational resources.